Measuring the Strength of Presidential Campaign Funding, Political Party Advertising Shopping 2024 - Junaedi (East Asian Journal of Multidisciplinary Research, 2024)
The General Election Commission has released a report on the campaign funds of the presidential and vice-presidential candidates for the 2024 election. Prabowo Subianto - Gibran Rakabuming Raka was recorded as the largest, far surpassing Ganjar Pranowo - Mahfud MD and Anies Baswedan - Muhaimin Iskandar.The advertisements were created to get the audience to increase the party's popularity. Golkar is the political party with the highest advertising spending on social media over the last three months, disbursing funds amounting to IDR 3.74 billion. This figure is quite far apart when compared to the advertising costs of other political parties. I am following in second place with a nominal advertising expenditure of IDR 785.6 million. National Awakening Party and Gerindra with advertising costs on social media amounting to IDR 195.7 million and IDR 49.18 million respectively.  PSI is in first place with the most advertisements, namely 1,277 advertisements on television amounting to IDR 42.84 billion, Perindo is in second place for the party with the most advertisements on TV, IDR. 82.73 billion and 1,220 advertisements. The electability of the political parties PDIP and Gerindra compete closely in the female voter group, these two parties were both chosen by 18.8% of female voter respondents. Gerindra's electability reached 19.5%, slightly ahead of PDIP which obtained 19.3%.  In the election of 5 major political parties, namely Gerindra, PDIP, Golkar, PKB and PKS, Gerindra was the party most chosen by young people under 30 years of age, with a vote share of 24.6%.